How Tupanvirus Degrades the Ribosomal RNA of Its Amoebal Host? The Ribonuclease T2 Track - Rolland, Clara; La Scola, Bernard; Levasseur, Anthony (Frontiers in Microbiology, 2020)
Tupanviruses are giant viruses recently discovered in Brazil from extreme environments: Tupanvirus soda lake (TPV-SL) and Tupanvirus deep ocean (TPV-DO). Unexpected features in Tupanviruses is the cytotoxic effect observed during infection, where the virus degrades the ribosomal RNA (rRNA) of its amoebal host. Interestingly, only TPV-SL causes this rRNA shutdown. We performed a genomic comparison of the two strains to determine potential modifications explaining the absence of rRNA degradation by TPV-DO. Whole genome comparisons were performed as well as more in-depth analysis at the gene level. We also calculated selective pressure on the orthologous genes between the two viruses. Our computational and evolutionary investigations revealed a potential target: a ribonuclease T2. These enzymes are known to be involved in cellular RNA catabolism such as in lysosomal degradation of rRNA. Our results suggest a functional ribonuclease localized in acid compartment closely related to ribonuclease T2 from eukaryotes. Silencing of the RNAse T2 gene of TPV-SL abolished its rRNA shutdown ability thereby correlating in silico assumption to the experimental evidence. In conclusion, all our results pointed to RNAse T2 as a target for explaining the difference for rRNA degradation ability between both strains.